Multi-objective immune-commensal-evolutionary programming for total production cost and total system loss minimization via integrated economic dispatch and distributed generation installation - Mansor M.H.; Musirin I.; Othman M.M. (MDPI, 2023)
Computer programming; Costs; Distributed computer systems; Distributed power generation; Electric load dispatching; Evolutionary algorithms; Immune system; Multiobjective optimization; Artificial Immune System; Distributed generation installation; Economic Dispatch; Economic dispatch problems; Multi objective; Multi-objectives optimization; Symbiotic organism search; Symbiotics; System loss; Total production cost; Scheduling